Enhancement of visible light mineralization ability and photocatalytic activity of BiPO4/BiOI - Liu, Yanfang; Yao, Wenqing; Liu, Di; Zong, Ruilong; Zhang, Mo; Ma, Xinguo; Zhu, Yongfa (Applied catalysis. B, Environmental, 2015)
•BiPO4/BiOI composite photocatalyst was synthesized via anion exchange method.•The photocatalytic activity of BiPO4/BiOI was increased by BiPO4.•The mineralization ability of BiPO4/BiOI was improved via charge transfer.•The mechanism for the enhanced photocatalytic performance was illustrated. Visible light mineralization ability is of great importance for the practical use of a photocatalyst. As a promising visible light photocatalyst, BiOI has relatively weak mineralization ability and is not efficient enough for the removal of some organic pollutants. In this work, the visible light mineralization ability of BiOI was improved via charge transfer between BiPO4 donor and BiOI acceptor. This charge transfer in BiPO4/BiOI composite photocatalyst produced more oxidative holes than that produced by pure BiOI, thus significantly improved its mineralization ability. Under visible light (λ>420nm) irradiation, the most effective BiPO4/BiOI could degrade phenol to small molecular organic acids more rapidly than BiOI and its removal efficiency for phenol and TOC were about 2 and 4 times as high as that of pure BiOI, respectively. The enhancement of photocatalytic performance is attributed to the enhanced oxidation ability of the hole and the increased separation and migration efficiency of photogenerated electrons and holes, which is resulted from the relatively large dipole moment of BiPO4.